Single-Cell Sequencing of Immune Cell Heterogeneity in IgG4-Related Disease - Wu, Xunyao; Peng, Yu; Li, Jieqiong; Zhang, Panpan; Liu, Zheng; Lu, Hui; Peng, Linyi; Zhou, Jiaxin; Fei, Yunyun; Zeng, Xiaofeng; Zhao, Yan; Zhang, Wen (Frontiers in Immunology, 2022)
Background The IgG4-related disease (IgG4-RD) is an immune-mediated disorder with fibrotic manifestations. However, the transcriptional profiles of immune cell subsets at single-cell level are unknown. Herein, single-cell sequencing was used to assess the specific cell subpopulations and pathways in peripheral blood mononuclear cells (PBMCs) of IgG4-RD. Methods Single-cell sequencing was performed using the PBMCs from four patients with IgG4-RD and three healthy controls (HCs). Functional enrichment and cell analysis were performed through re-clustering of PBMCs to assess functional pathways and intercellular communication networks in IgG4-RD. Western blot and flow cytometry were used to verify sequencing and functional enrichment results. Results Four major cell types and 21 subtypes were identified. Further subclustering demonstrated that plasma B-cell proportions increased with increasing glycolysis/gluconeogenesis activity in IgG4-RD. Re-clustering of myeloid cells showed that EGR1 and CD36 expressions were significantly increased in CD14+ monocytes of IgG4-RD, as validated by Western blot analysis. Moreover, tumor necrosis factor (TNF) production pathways were positively regulated in CD14+ monocytes of IgG4-RD. In vitro stimulation showed that CD14+ monocytes of IgG4-RD could secrete higher levels of TNF-α . Notably, the proportions of CD8 central memory T (TCM) and TIGIT+ CD8 cytotoxic T (CTL) increased in patients with IgG4-RD compared with HCs. Further interaction analysis showed that B cell activation factor (BAFF) signaling pathways were enriched from myeloid cells subsets to B cells. Conclusion This study enhances the understanding of the cellular heterogeneity and transcriptional features involved in the pathogenesis of IgG4-RD, providing key clinical implications.